2018
DOI: 10.21037/jtd.2018.04.98
|View full text |Cite
|
Sign up to set email alerts
|

TP53 mutations predict for poor survival in ALK rearrangement lung adenocarcinoma patients treated with crizotinib

Abstract: mutations reduce responsiveness to crizotinib and worsen prognosis in rearrangement NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 26 publications
4
30
0
Order By: Relevance
“…In this study, we were able to obtain only one postbiopsy from a patient with acquired resistance and an ALK-G1220R mutation was detected which is known to induce crizotinib resistance. Recent studies showed a clear association between TP53 mutation and worse PFS (23,27), and we were able to observe a similar effect in our cohort with 3 of 3 intrinsically Cou€ etoux du Tertre et al…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, we were able to obtain only one postbiopsy from a patient with acquired resistance and an ALK-G1220R mutation was detected which is known to induce crizotinib resistance. Recent studies showed a clear association between TP53 mutation and worse PFS (23,27), and we were able to observe a similar effect in our cohort with 3 of 3 intrinsically Cou€ etoux du Tertre et al…”
Section: Discussionsupporting
confidence: 86%
“…In contrast to previously published work (29,30), specific EML4-ALK variants were not sufficient to explain patient response to crizotinib in our cohort. In addition, the article highlights novel concurrent genomic events (loss of ALK and gain of EGFR) only present in intrinsically resistant patients and confirmed unfavorable association between ALK rearrangement and TP53 mutation for patient outcome (23,27). Because of the small sample size in our study, further validation will be essential to confirm our observations in crizotinib or other ALK-TKI-treated patients with ALKþ NSCLC.…”
Section: Discussionsupporting
confidence: 60%
“…14 A recent study revealed that TP53 mutations reduced responsiveness to crizotinib and worsened prognosis in patients with ALK-rearranged NSCLC. 15 We found that 41.7% CSF samples harbored TP53 compared with 27.3% of plasma samples. The higher rate of TP53 in CSF might be related to resistance and the emergence of LM.…”
Section: Discussionmentioning
confidence: 64%
“…The present data provide a novel insight into the differences in prognosis between EML4-ALK variant V1 and variant V3 patients. A number of studies have demonstrated that TP53 mutations predict a poor outcome following systemic therapy for ALK fusion NSCLC, and coalterations between EML4-ALK variant V3 and TP53 mutations define a patient subset with worse prognosis [55][56][57]. The present study demonstrated that the frequency of concurrent TP53 mutations and EML4-ALK variant V3 was markedly higher compared with that of concurrent TP53 mutations and EML4-ALK variant V1, which indicates that TP53 mutation may be one of the critical reasons for the differences in prognosis between patients with EML4-ALK variant V1 and variant V3 NSCLC.…”
mentioning
confidence: 99%